MICROELECTRONIC SELF-OSCILLATING OPTICAL POWER TRANSDUCERS - OSADCHUK, IAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Microelectronic self-oscillating optical power transducers are proposed based on microelectronic transistor structures with differential negative resistance and a primary photosensitive element based on bipolar and field-effect phototransistors, and the primary photosensitive elements are also active elements of the self-oscillators themselves, which greatly simplifies the conversion design.Based on the consideration of physical processes in the primary photosensitive element and self-oscillator, a mathematical model of a microelectronic optical transducer was developed, on the basis of which the parametric dependences of the conversion and sensitivity functions were obtained. The main factor in changing the conversion function and sensitivity is the change in optical power. This changes the equivalent capacitance and differential negative resistance of the oscillatory system of the microelectronic self-oscillating optical power transducer, changing the output frequency of the device. Since the optical power varies in the range of 0…90 μW/cm2, the sensitivity of the optical transducer varies from 151.3 kHz/μW/cm2 to 215.2 kHz/μW/cm2. Analytical expressions for the parametric dependence of the sensitivity and conversion functions are obtained, demonstrating the possibility of an easier calculation of the main characteristics of the transducer, taking into account the influence of each parameter of the primary photosensitive element and the parameters of the self-oscillator on the output frequency of the device in comparison with the calculations of these parameters with systems of Kirchhoff equations. Photosensitive transducers with frequency output do not need analog-to-digital transducers or amplifiers for further processing of the information signal, which significantly reduces the cost of information and measuring equipment. In addition, when the transducers operate at very high frequencies, it is possible to directly transmit information over a distance.
Keywords: optical transducer; differential negative resistance; frequency; self-oscillator; photosensitive transistor